CGIAR Research Program on Policies, Institutions, and Markets - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
The CGIAR Research Program on Policies, Institutions, and Markets (PIM) leads action-oriented research for a food-secure present and future. Our research provides support for policies that help poor farmers, both men and women, improve their lives; produce nutritious and affordable foods; and protect the soil, water, and biodiversity in rural landscapes.